2011
DOI: 10.1007/s00296-011-1909-8
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of sarcoidosis in a child

Abstract: Sarcoidosis is a chronic multisystemic granulomatous disease of unknown etiology. We report a 5-year-old boy with sarcoidosis who had an unusual presentation of membranous nephropathy and Budd-Chiari syndrome. These combinations of features have never reported in pediatric literature so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…12 On the other hand, treatment of BCS is better codified, based on anticoagulation therapy and treatment of the underlying condition; in case of failure, transjugular intrahepatic portosystemic shunt (TIPS) insertion and liver transplantation should be considered. 14 Regarding previous reported cases of BCS associated with sarcoidosis: 3 patients were treated with corticosteroids for liver involvement 5 , 7 , 8 associated with anticoagulation in one case 8 while 3 patients had liver transplantation (after TIPS failure for one) 3 , 6 , 9 and the 2 former had surgical portosystemic shunt. 10 , 11 Thus, this is the second case of BCS complicating hepatic sarcoidosis treated with anticoagulation and corticosteroids.…”
Section: Discussionmentioning
confidence: 98%
“…12 On the other hand, treatment of BCS is better codified, based on anticoagulation therapy and treatment of the underlying condition; in case of failure, transjugular intrahepatic portosystemic shunt (TIPS) insertion and liver transplantation should be considered. 14 Regarding previous reported cases of BCS associated with sarcoidosis: 3 patients were treated with corticosteroids for liver involvement 5 , 7 , 8 associated with anticoagulation in one case 8 while 3 patients had liver transplantation (after TIPS failure for one) 3 , 6 , 9 and the 2 former had surgical portosystemic shunt. 10 , 11 Thus, this is the second case of BCS complicating hepatic sarcoidosis treated with anticoagulation and corticosteroids.…”
Section: Discussionmentioning
confidence: 98%
“…In their study, Chau et al [14] found periportal hyperechogenicity in 15 patients (30%) who presented with recurrent pyogenic cholangitis. Finally, hyperechogenicity was also recorded in patients with dengue fever [15], chikungunya virus-induced acute arthritis [16], leptospirosis [17], and febrile attacks of sarcoidosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2 pediatric cases of BCS were described to be associated with hepatic sarcoidosis; 1 was treated with corticosteroids, whereas the other was initially treated with a TIPS, complicated by recurrent thrombosis which eventually required liver transplantation. 16,17…”
Section: Discussionmentioning
confidence: 99%